Role of scalar mesons in the beam asymmetry of p¯p and Λ¯Λ photoproduction at JLab; Physical Review D; Vol. 96, iss. 5 - Gutsche T. Thomas; Kuleshov S. V. Sergey Vasiljevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Obukhovsky I. T. Igor Timofeevich (2017, 2017)
Title screen